RELIGION AND LOCAL WISDOM AS SOCIAL CAPITAL TO FACING RECESSION DUE TO PANDEMIC - Muhammad Agus Noorbani; Mahmudah Nur; Nurrahmah Nurrahmah; Agus Iswanto (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
The Covid-19 pandemic has impacted to various fields of human life, including social and economic. The government has made various efforts to stimulate the community's economy, initiating various groups and individuals with various values of wisdom to revive their economy. This study aims to determine local wisdom and religious values that have an impact on community efforts in dealing with the Covid-19 pandemic; the process of using religious wisdom in the local realm in handling a pandemic; The impact of local wisdom and religion on the development of social capital in various aspects of people's lives. Based on qualitative data collected through interviews and observation in four provinces; West Java, Centra Java, DI Yogyakarta, and Bali this study found that the local wisdom behind various sharing activism during the pandemic comes from traditional values that have long been practiced by residents in various research areas. Their shared activism is a form of their ability to adapt various noble and traditional values in today's highly chaotic situation. Various sharing activism during the pandemic has established relationships among fellow citizens.